2012
DOI: 10.1371/journal.pcbi.1002472
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Provider Recruitment for Influenza Surveillance Networks

Abstract: The increasingly complex and rapid transmission dynamics of many infectious diseases necessitates the use of new, more advanced methods for surveillance, early detection, and decision-making. Here, we demonstrate that a new method for optimizing surveillance networks can improve the quality of epidemiological information produced by typical provider-based networks. Using past surveillance and Internet search data, it determines the precise locations where providers should be enrolled. When applied to redesigni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…Past work on infectious disease surveillance has focused at the statelevel (Polgreen et al 2009;Scarpino et al 2012) or assumed that risk was evenly spread across well-mixed populations (Pelat et al 2014). Surveillance studies focused on broader definitions of health and on chronic diseases have found similar disparities to the ones presented here (Liao et al 2004;Kandula et al 2007).…”
Section: Introductionmentioning
confidence: 76%
“…Past work on infectious disease surveillance has focused at the statelevel (Polgreen et al 2009;Scarpino et al 2012) or assumed that risk was evenly spread across well-mixed populations (Pelat et al 2014). Surveillance studies focused on broader definitions of health and on chronic diseases have found similar disparities to the ones presented here (Liao et al 2004;Kandula et al 2007).…”
Section: Introductionmentioning
confidence: 76%
“…Here, we showed that bias due to variations in local GP density around participants could be reduced using weighted estimators, and supported this conclusion with empirical evidence. This approach could be used to introduce more flexibility for developing algorithms to identify the best placement of data providers [37]. …”
Section: Discussionmentioning
confidence: 99%
“…In this last respect, seemingly reasonable solutions may have undesirable features: we found here that selecting one GP in each of the 100 largest French towns would lead to large underestimation of incidence. Several approaches have been described to the optimal selection of data providers in surveillance, taking into account spatial coverage or representativeness of monitored population [37]. In our experience, the effective use of such approaches in GP based surveillance is difficult as it is not possible to have a stable roster of GPs who want to participate in surveillance [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, NDS have facilitated expansion of dengue and influenza surveillance to countries without infrastructure capable of real time surveil-lance [5, 17, 21, 22]. This has also been done in the context of hospitalizations in Texas [23], mental illness, psychological manifestations of physical morbidities [24, 25], and search queries from clinical decision support sites, such as UpToDate [26]. In these cases, although NDS-based systems are being asked to estimate data that is actually being collected, those data are not available quickly enough for use in public health decision making.…”
Section: How Does Nds Integrate Into the Surveillance Ecosystem?mentioning
confidence: 99%